Impact of the inflow of Vistula river waters on the pelagic zone in the Gulf of Gdańsk - Nadezhda Torgunova; Natalia Lapina; Mariusz Zalewski; Alina Agatova; Lena Szymanek; Krzysztof Rychert; Janina Kownacka; Anetta Ameryk; Anna Jarosiewicz; Magdalena Wielgat-Rychert (Oceanologia)
The biomass, production, composition of autotrophic phytoplankton andhetero-trophic bacteria were studied along with environmental and biologicalparameters. Samples were taken from Vistula river water (at Kiezmark) andfrom the river plume to the outer stations in the Gulf of Gdańsk (Baltic Sea) in June2005. The phytoplankton biomass gradient appeared to be simply the result ofdilution of the river water in the sea water, whereas the bacterial abundanceand biomass dropped between the river station and the first sea water stations,a decrease that cannot be explained by the dilution effect. The Vistula waterstimulated the production mainly of bacterioplankton but also of phytoplanktonin the river plume as compared to rates measured in Vistula waters and at the opensea stations. However, this stimulation did not result in a measurable increasein biomasses, probably because of the short retention time of water in theriver plume. Phytoplankton production was correlated with phytoplankton biomass(Chl a), while bacterial production was correlated with phytoplanktonproduction and phytoplankton biomass (Chl a).